Behavioral Analysis of MSME Owners in Subang Regency to Adopt Islamic P2P Lending Platform - Elsa Hapsari, Renata; Rahadian, Dadan (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Technological advancements are fostering financial growth and inclusion in this era of globalization, particularly for Islamic P2P lending companies in Indonesia. Islamic P2P lending provides MSMEs with easier access to financing. However, to enhance its development by connecting between MSME needs and services offered by Islamic P2P lending providers. The objective of this study is to analysis MSME owner’s behavior and their interest in adopting Islamic P2P lending platforms, especially in rural areas. UTAUT2 model is utilized in this study. Data were collected from 104 MSME owners as respondents through a questionnaire survey, then analyzed using PLS-SEM techniques. Within eight constructs tested, there are four constructs that have a significant effect including Hedonic motivation, Price Value, Habit, and Perceived Security & Risk. Age moderates the Hedonic Motivation while Gender has no moderating effect. R-square of the inner model test is 0.640. The insights and findings of this study can be beneficial for Islamic P2P lending companies in Indonesia by identifying key factors that influence MSMEs' decisions to adopt the platforms.